Phenotypic and Marker-Assisted Genetic Enhancement of Parental Lines of Rajalaxmi, an Elite Rice Hybrid - Dash, Amit K.; Rao, Ravi N.; Rao, G. J. N.; Verma, Ram L.; Katara, Jawahar L.; Mukherjee, Arup K.; Singh, Onkar N.; Bagchi, Torit B. (Frontiers in Plant Science, 2016)
The cytoplasmic male sterile line system comprising CRMS 32A and its maintainer line CRMS 32B is a popular choice for the development of new hybrids in India as CRMS 32A, having Kalinga 1 cytoplasm (other than WA), is a viable alternative to WA cytoplasm. However, both lines are susceptible to bacterial blight (BB), a major disease on rice. As enhancement of host plant resistance is the most effective and economical strategy to control this disease, four resistance genes (Xa4, xa5, xa13 and Xa21) were transferred from a BB pyramid line of IR64, into the A and B lines using a marker-assisted backcrossing (MAB) breeding strategy. During the transfer of genes into CRMS 32B, foreground selection was applied using markers associated with the genes, and plants having resistance alleles of the donor, are selected. Selection for morphological and quality traits was practiced to select plants similar to the recurrent parent. The four gene and three gene pyramid lines exhibited high levels of resistance against the BB pathogen when challenged with eight virulent isolates. Using genome wide based SSR markers for background selection, pyramids having >95% of the recurrent parent genome were identified. With CRMS 32B gene pyramid as donor, the four resistance genes were transferred into the A line through repeated backcrosses and the A line pyramids also exhibited high level of resistance against BB. Through a combination of selection at phenotypic and molecular levels, four bacterial blight resistance genes were successfully introduced into two parental lines (CRMS 32 B and A) of Rajalaxmi, an elite popular hybrid. The pyramided B lines did exhibit high levels of resistance against BB. Selection for morphological and quality traits and background selection hastened the recovery of the recurrent parent genome in the recombinants. Through repeated backcrosses, all the four resistance genes were transferred to CRMS 32A and test crosses suggest that the maintenance ability of the improved CRMS 32B lines is intact. These improved maintainer and CMS lines can directly be used in hybrid rice breeding and the new hybrids can play an important role in sustainable rice production in India.